{
x
+
5
=
3
y
−
4
2
(
3
y
−
4
)
=
3
x
+
7
Expand the expression
Apply the
Distributive Property
{
x
+
5
=
3
y
−
4
6
y
−
8
=
3
x
+
7
{
x
+
5
=
3
y
−
4
6
y
−
8
=
3
x
+
7
Rearrange the terms
Rearrange variables to the left side of the equation
{
x
−
3
y
=
−
4
−
5
6
y
−
3
x
=
7
+
8
{
x
−
3
y
=
−
4
−
5
6
y
−
3
x
=
7
+
8
Calculate
Calculate the sum or difference
{
x
−
3
y
=
−
9
6
y
−
3
x
=
15
{
x
−
3
y
=
−
9
6
y
−
3
x
=
15
Reorder the equation
Reorder the equation
{
x
−
3
y
=
−
9
−
3
x
+
6
y
=
15
{
x
−
3
y
=
−
9
−
3
x
+
6
y
=
15
Rearrange the terms
Rearrange like terms to the same side of the equation
{
x
=
−
9
+
3
y
−
3
x
+
6
y
=
15
{
x
=
−
9
+
3
y
−
3
x
+
6
y
=
15
Substitute
Substitute into one of the equations
−
3
(
−
9
+
3
y
)
+
6
y
=
15
−
3
(
−
9
+
3
y
)
+
6
y
=
15
6 steps
Solve the equation
Apply the
Distributive Property
27
−
9
y
+
6
y
=
15
Combine like terms
Combine like terms
27
−
3
y
=
15
Rearrange variables to the left side of the equation
Rearrange variables to the left side of the equation
−
3
y
=
15
−
27
Calculate the sum or difference
Calculate the sum or difference
−
3
y
=
−
12
Divide both sides of the equation by the coefficient of variable
Divide both sides of the equation by the coefficient of variable
y
=
−
3
−
12
2 steps
Determine the sign for multiplication or division
y
=
3
12
Cross out the common factor
y
=
4
Cross out the common factor
y
=
4
Calculate
y
=
4
y
=
4
Substitute
Substitute into one of the equations
x
=
−
9
+
3
×
4
x
=
−
9
+
3
×
4
Solve the equation
Calculate
x
=
3
x
=
3
Write the solution
The solution of the system is
{
x
=
3
y
=
4
{
x
=
3
y
=
4
Answer
{
x
=
3
y
=
4